Blockchain-as-a-Service (BaaS) Empowered Vendor-Managed Inventory (VMI): A Paradigm Shift in Supply Chain Efficiency - Sanjay Vijay Mhaskey (The Journal of The British Blockchain Association)
This article explores how Blockchain-as-a-Service (BaaS) can revolutionise Vendor-Managed Inventory (VMI) models. VMI is a supply chain approach where vendors manage customer inventory levels. However, traditional VMI models face challenges in data sharing, integration, real-time access, security, and enforcing service agreements. To overcome these limitations, this paper suggests using BaaS to implement VMI with blockchain technology. The utilisation of BaaS in VMI processes allows organisations to utilise blockchain’s attributes, including trust-less collaboration, real-time data access, heightened security, data integrity, immutability, and automation through smart contracts. The article explains how BaaS platforms offer streamlined provisioning, easy configuration, rapid member onboarding, and seamless integration with existing systems. Furthermore, it highlights the benefits of using BaaS to enhance supply chain efficiency by facilitating smooth collaboration among VMI stakeholders. In addition to these benefits, the proposed solution emphasises the use of built-in functions within each partner’s ERP/supply chain/enterprise applications, combined with blockchain integration capability, to establish a comprehensive end-to-end VMI solution. Moreover, the article provides a conceptual model of the solution that covers an end-to-end VMI process. It also provides guidelines for selecting a suitable BaaS provider tailored to VMI implementation. Through these contributions, the article proposes an innovative VMI model built upon BaaS foundations, effectively addressing the inefficiencies of traditional VMI, and ushering in a new era of optimised supply chain performance.